Swallow the Ghost - Montague, Eugenie (New York : Mulholland Books, 2024)
"Things are going well for Jane Murphy, or so it seems. She's making it in New York, a sort of wunderkind at the social media marketing startup where she works. She's put an experimental writer, Jeremy Miller, on the map by helping him concoct a viral internet novel, told in fragments through various fake social media accounts. But privately, Jane feels trapped, ruled by her routines and her compulsions with food and social media, caught up in an endless cycle of soothing and punishing herself. There is so much that she has to keep hidden, especially from Jeremy as their professional relationship transforms into something more. But then, tragedy strikes, and the story changes track. As the perspective shifts, so too does our image of Jane and those in her orbit as what we think we know begins to unravel. Audacious, emotionally precise and head-spinning in its ingenuity, Swallow the Ghost interrogates our public identities and private realities through the kaleidoscopic portrait of one woman's life."--Provided by publisher.
new book 2024 fall.
Includes bibliographical references.
Keywords: Identity (Psychology) -- Fiction; Women -- Fiction; Social media -- Fiction; Humorous; Thrillers; Technological; Private investigators; dark humor; Mystery and detective stories; Psychological fiction; Detective and mystery fiction; Detective fiction; Mystery fiction